Conceptual challenges to the harm threshold - Taylor, Maggie (Bioethics, 2020)
Children are presumptively regarded as incompetent to make their own medical decisions, and the responsibility for making such decisions typically falls to parents. Parental authority is not unlimited, however, and ethical guidelines identifying appropriate bounds on this authority are needed. One proposal currently gaining support is the harm threshold (HT), which asserts that the state may only legitimately intervene in parental decision-making when serious and preventable harm to children is likely. This paper considers two questions: in virtue of what underlying principle or property does the HT gain its purported justification?; and does this underlying principle or property ground the HT as its proponents conceive of it? I identify two separate grounds represented in the literature: (a) J.S. Mill’s Harm Principle; and (b) the liberty interests of parents. I find that the HT is not sufficiently grounded in either of these, revealing a substantial conceptual difficulty for its advocates.